61 Targeting Elderly Patients on Inhaled Corticosteroids for Respiratory Optimisation. (6th February 2020) - Wicks, L; Kubler, A; Robinson, P
Abstract: Introduction: Inhaled corticosteroids (ICS) are associated with increased rates of pneumonia, fracture and diabetes. ICS have limited short and long term benefits in COPD, and cessation of steroids in selected patients has been proven safe. We observed that a large proportion of inpatients in the geriatric service were prescribed ICS, and we aimed to review the reasoning for this and introduce a program of respiratory review in order to optimise care in these patients. Methods: We conducted a retrospective audit of patients discharged from a geriatric service over a 3 month period. Sequential discharges were assessed for the presence and type of inhaled therapies, the documented diagnosis. After identifying high rates of inhaled therapy usage, we undertook a series of quality improvement interventions aimed at optimising respiratory care in these elderly patients. This included a guideline based protocol for reviewing respiratory diagnoses and prescriptions. Results: In the retrospective analysis, 67/297 (22.5%) patients were discharged on inhaled therapy. 55/67 (82%) were discharged on an ICS, of which 20/67 (36%) were on high doses, equivalent to >1000micrograms of beclomethasone. Very few of these patients had evidence of inhaled therapy review during admission. 15/55 of these patients were given a discharge diagnosis of pneumonia; whilst only 6/55 were admitted with an exacerbation of their COPD. Our preliminary data suggest that a single paged protocol aimed at improving adherence to best practice lead to practice change: Dose modification has occurred in 50% of patients on ICS, leading to a reduction in steroid burden, and an annual reduction in prescription costs of £75 per patient reviewed. None of these patients have been re-admitted with respiratory exacerbations. Conclusions: By introducing measures to assist in the review and modification of inhaled therapies, we were able to change practice. The alteration in practice led to reduction in prescription costs, and a reduced burden of inhaled corticosteroids. We propose that widespread encouragement of geriatrician led respiratory review could lead to harm reduction and cost saving in elderly inpatients.